The old and the death - Vianna, Lucy Gomes (2013)
The old age acceptance leads to the recognition of their own limitations and of their finitude, which has no definite beginning but has an ending clearly established: the death. In today's society, the order is silence when the focus is the death and also the old age, because this is regarded as its harbinger. Thus, it is important that health professionals in the care of the elderly should not remain silent on the question of death. This issue should be addressed naturally, because as people become aware of their finitude, they understand life in its complexity and may revise their values.